Vibriosis Outbreaks in Aquaculture: Addressing Environmental and Public Health Concerns and Preventive Therapies Using Gilthead Seabream Farming as a Model System - Sanches-Fernandes, Gracinda M. M.; Sá-Correia, Isabel; Costa, Rodrigo (Frontiers in Microbiology, 2022)
Bacterial and viral diseases in aquaculture result in severe production and economic losses. Among pathogenic bacteria, species belonging to the Vibrio genus are one of the most common and widespread disease-causing agents. Vibrio infections play a leading role in constraining the sustainable growth of the aquaculture sector worldwide and, consequently, are the target of manifold disease prevention strategies. During the early, larval stages of development, Vibrio species are a common cause of high mortality rates in reared fish and shellfish, circumstances under which the host organisms might be highly susceptible to disease preventive or treatment strategies such as vaccines and antibiotics use, respectively. Regardless of host developmental stage, Vibrio infections may occur suddenly and can lead to the loss of the entire population reared in a given aquaculture system. Furthermore, the frequency of Vibrio–associated diseases in humans is increasing globally and has been linked to anthropic activities, in particular human-driven climate change and intensive livestock production. In this context, here we cover the current knowledge of Vibrio infections in fish aquaculture, with a focus on the model species gilthead seabream (Sparus aurata), a highly valuable reared fish in the Mediterranean climatic zone. Molecular methods currently used for fast detection and identification of Vibrio pathogens and their antibiotic resistance profiles are addressed. Targeted therapeutic approaches are critically examined. They include vaccination, phage therapy and probiotics supplementation, which bear promise in supressing vibriosis in land-based fish rearing and in mitigating possible threats to human health and the environment. This literature review suggests that antibiotic resistance is increasing among Vibrio species, with the use of probiotics constituting a promising, sustainable approach to prevent Vibrio infections in aquaculture.